Luxembourg : 2022 Article IV Consultation-Press Release; and Staff Report for Luxembourg. (IMF Staff Country Reports; Country Report ;, 2022)
Real GDP surpassed its pre-pandemic trend in early 2021, and the labor market is tight. Inflation is increasing, mainly driven by energy prices, but core inflation is also edging up. The fiscal position strengthened and the financial sector has remained resilient. Rapidly growing housing prices raise concerns about affordability and could pose risks for financial stability and the country's attractiveness in the medium term. Following the outbreak of war in Ukraine, inflation pressures have intensified and financial market volatility has risen.